Sub-groups (profiles) of individuals experiencing post-traumatic growth during the COVID-19 pandemic - Blom, Denise M.; Sulkers, Esther; Post, Wendy J.; Schroevers, Maya J.; Ranchor, Adelita V. (Frontiers in Psychology, 2022)
Objective. Some people experience post-traumatic growth (PTG), entailing positive changes such as a greater appreciation of life following traumatic events. We examined PTG in the context of the negative consequences of the COVID-19 pandemic, notably working from home and social distancing. We aimed to assess whether distinct sub-groups (profiles) of individuals experiencing PTG could be identified by how they appraised and coped with the COVID-19 pandemic. Method. For this cross-sectional study, we used convenience sampling. In total, 951 participants from the general population completed an online questionnaire with items focusing on primary and secondary appraisal, positive reappraisal, rumination, and coping flexibility. For the latent profile analysis, we selected a sample of 392 individuals who had experienced moderate degrees of pandemic-related PTG, reporting at least two of the 10 positive changes in the Post-Traumatic Growth Inventory-Short Form. Results. We identified two distinct profiles among people experiencing PTG. The first was characterised by low levels of primary and stressfulness and higher levels of secondary appraisal (e.g., resilient group), increased coping flexibility and greater use of positive reappraisal. The second was characterised by higher levels of stressfulness and primary appraisals (e.g., stressed group) and greater use of rumination. Conclusion. The two sub-groups evidently appraised and coped with the COVID-19 pandemic differently. Therefore, future research should account for these different profiles of people experiencing PTG.